2015
DOI: 10.1186/s13049-015-0158-3
|View full text |Cite
|
Sign up to set email alerts
|

Patients presenting at the emergency department with acute abdominal pain are less likely to be admitted to inpatient wards at times of access block: a registry study

Abstract: BackgroundAlso known as access block, shortage of inpatient beds is a common cause of emergency department (ED) boarding and overcrowding, which are both associated with impaired quality of care. Recent studies have suggested that access block not simply causes boarding in EDs, but may also result in that patients are less likely to be admitted to the hospital from the ED. The present study’s aim was to investigate whether this effect remained for patients with acute abdominal pain, for which different managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The number of boarding patients gradually increases from Monday to Friday, and then decreases on Friday afternoon. The median (IQR) value was 56 (44-68) for the total number of patients, 35 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) for the number of evaluating patients, and 14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) for the number of boarding patients. Therefore, the third quartile, the critical point of overcrowding was 68, 44, and 26, for total, evaluating, and boarding indicators, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of boarding patients gradually increases from Monday to Friday, and then decreases on Friday afternoon. The median (IQR) value was 56 (44-68) for the total number of patients, 35 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) for the number of evaluating patients, and 14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) for the number of boarding patients. Therefore, the third quartile, the critical point of overcrowding was 68, 44, and 26, for total, evaluating, and boarding indicators, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulation of boarding patients in the ED implies that the ED output is blocked, which is directly affected by the in-hospital bed occupancy [26,27]. If the inpatient occupancy rate is too high and the ED is overcrowded with boarding patients awaiting hospital beds, emergency doctors become more careful when making a decision for additional admissions and decide to transfer some patients to other hospitals or plan discharge and short-term follow-up for patients with relatively mild conditions [28][29][30]. Previous studies have reported that high in-hospital bed occupancy reduced the number of patients admitted through the ED [29,31].…”
Section: Discussionmentioning
confidence: 99%
“…Strata were proposed prior to analysis. Since 95 % reflects the median occupancy at the hospital, <95 % was used as a commonsense reference [ 26 ]. Proportions of patients experiencing each outcome were compared across strata using Fisher’s exact test.…”
Section: Methodsmentioning
confidence: 99%
“…As medicine still is organised around specialties and organ systems, we hope that these more specific results will help build awareness and make valuable additions to previous findings of a more general nature, such as premature hospital discharges, declining mental health in staff and delays in emergency care delivery. [16][17][18][32][33][34][35][36][37][38] Profound variation in the likelihood of direct SU admission from the ED among the study sites (adjusted for bed occupancy), indicate that the capabilities of hospitals to handle bed crises differ. One hypothesis is that this stems from differences in local and regional stroke care traditions and in adherence to national guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…4,[8][9][10] While a link between hospital bed shortages and ED overcrowding is already established, recent publications suggest additional associations with decreased overall hospital admission rates from the ED and premature hospital discharges. [11][12][13][14][15][16][17][18] In an attempt to elaborate the effects of hospital crowding in patients with acute stroke, this study aims at measuring the association between hospital bed occupancy and the likelihood of direct admission to a SU from the ED. A secondary objective is to investigate whether the likelihood of direct SU admission varies across study sites.…”
Section: Introductionmentioning
confidence: 99%